AN OVERVIEW OF MINIMUM WAGE IN NIGERIA: A THEORETICAL REVIEW - Hyelkuzuku Ibrahim, Ezekiel; Tanimu, Audu; Dokan Ezekie, Williams (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
One of the duties of government is to ensure the welfare of her citizens. This is also reflected in Nigerian constitution in Section 14(b) of the 1999 constitution which states that the security and welfare of the people shall be the primary purpose of government. The idea of minimum wage has been a contending issue Nigeria due to poor under understanding between policy makers and the labour force. Wages and salaries constitute a significant part in total cost of operations in any organisation. The general objective of the study is to examine the effect of minimum wage in Nigeria Public sector. The target population of the study rest on various Public sector workers in Nigeria. The study use simple random sampling in which 400 public sector workers in Gombe are sampled. Data is collected using structured questionnaire. Through the field study it was discovered that the effects of minimum wage on workers tends to increase their standard of living, working morale and employees development to better their services to the government. Conclusively, the prevailing minimum wages paid by the three tiers of government are grossly inadequate compared to the sustainable budgets for all the family income levels. The study recommends that government insincerity on agreements with labour unions should be corrected so as to serve as motivations to job seekers and low income earners in Nigeria.